Muscle Oxygenation, Heart Rate, and Blood Lactate Concentration During Submaximal and Maximal Interval Swimming - Dalamitros, Athanasios A.; Semaltianou, Eleni; Toubekis, Argyris G.; Kabasakalis, Athanasios (Frontiers in Sports and Active Living, 2021)
This study aimed to determine the relationship between three testing procedures during different intensity interval efforts in swimming. Twelve national-level swimmers of both genders executed, on different occasions and after a standardized warm-up, a swimming protocol consisted of either a submaximal (Submax: 8 efforts of 50 m) or a maximal interval (Max: 4 efforts of 15 m), followed by two series of four maximal 25-m efforts. Near-infrared spectroscopy in terms of muscle oxygen saturation (SmO2), heart rate (HR), and blood lactate concentration (BLa) were analyzed at three testing points, after the Submax or the Max protocol (TP1), after the 1st 4 × 25-m (TP2), and the 2nd maximal 4 × 25-m set (TP3). BLa and HR showed significant changes during all testing points in both protocols (P≤0.01; ES range: 0.45 to 1.40). SmO2 was different only between TP1 and TP3 in both protocols (P≤0.05 - 0.01; ES range: 0.36 to 1.20). A large correlation during the Max protocol between SmO2 and HR (r: 0.931; P≤0.01) and between SmO2 and BLa was obtained at TP1 (r: 0.722; P≤0.05). A range of moderate-to-large correlations were revealed for SmO2 / HR, and BLa / HR for TP2 and TP3 after both protocols (r range: 0.595 to 0.728; P≤0.05). SmO2 is a novel parameter that can be used when aiming for a comprehensive evaluation of competitive swimmers’ acute responses to sprint interval swimming, in conjunction with HR and BLa.